Plastic deformation phenomena during cold spray impact of WC-Co particles onto metal substrates. (1st February 2017) - Dosta, S.; Bolelli, Giovanni; Candeli, Alessia; Lusvarghi, Luca; Cano, Irene Garcia; Guilemany, Josep Maria
Abstract: This paper studies the plastic deformation phenomena in ductile substrates (Al7075 alloy, carbon steel) during cold spray-deposition of WC-Co. Metallographic inspection of etched cross-sections and through-thickness nano-hardness profiling indicate that plastic deformation of the substrate (into which undeformed WC-Co particles penetrate deep) is confined to a shallow area, below which the material appears unaltered. Adiabatic deformation phenomena in the substrate are revealed by finite element modelling of the impact process. Close to the surface, the temperature raises in less than 10 ns, leading to metal jetting, whilst the underlying material, below a depth of few micrometres, is substantially unaffected. Graphical abstract: Image 1